Parental Involvement in Young Learners’ Speaking: A Qualitative Study on Learner Performance and Classroom Instruction - Rowiyah, Siti; Fitriani, Aries; Anam, Khoirul (Journal of Languages and Language Teaching, 2024)
Parental involvement can be seen in parental practices to help children’s academic and intellectual activities. There is a correlation between parental engagement and motivation enhancement, favorable views toward language acquisition, and improved self-confidence in children. Therefore, the present study investigates the impact of parental involvement on young learners' speaking performance and classroom instruction in English as a Foreign Language. Using a qualitative, grounded theory approach, the study involves English teachers of young learners and parents of children aged seven to ten years old who learn English as a foreign language. Findings reveal that students with parental supervision demonstrated increased engagement and superior English pronunciation skills. Parents primarily employ a parenting style supported by Mobile Assisted Language Learning (MALL), using verbal communication, drilling exercises, and digital materials. Interestingly, parents often rely on teachers' autonomy in selecting appropriate instruction due to psychological considerations, fearing inconvenience if they intervene in teaching strategies. In response, teachers incorporate novel strategies to meet parents' expectations and address their concerns. The study suggests that engaging parental involvement in young learners' language learning brings beneficial effects for optimum child language acquisition. These findings highlight the complex interplay between parental involvement, teaching strategies, and young learners' language development, emphasizing the importance of collaborative efforts between parents and teachers in fostering effective English language learning environments.